(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: This paper aims to show the reasons for the occasional use of the plea bargain, which has been in use for three years. Methodology: The authors conducted interviews with prosecutors, investigators, examiners, judges, and defense lawyers, reviewed publications on the legal instrument, and examined available statistical data on plea bargaining. Findings: Plea bargaining is an old and new legal instrument in the current Criminal Procedure Code. It is the predecessor of the former waiver of trial, which was rarely used by prosecutors despite repeated amendments to the law and thus failed to fulfill the hopes of speeding up criminal proceedings and reducing the burden on the courts. The new instrument, which is regulated differently from its predecessor, was expected to increase the frequency of use. The authors’ assumptions were confirmed, and the study provides statistical evidence of the infrequent use of the system: in 2020, only 0.0012% of indictments were based on plea bargaining. The reasons for the infrequent use of the system include the fact that in prosecutorial practice, the institution of the cooperating accused is used instead of plea bargaining, or an informal promise is made on the content of the charge if the suspect confesses. The institution would require more attention from the investigating authority, and the plea bargaining position is also difficult for the defense. The authors conclude that plea bargaining for statistical reasons alone is not a step in the right direction. Value: The paper could contribute to changes in the practice of legal practitioners and more frequent use of the legal instrument of conciliation. Monitoring changes could be the subject of other papers.